If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3x = -3x + 16 Reorder the terms: 4 + 3x = 16 + -3x Solving 4 + 3x = 16 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 4 + 3x + 3x = 16 + -3x + 3x Combine like terms: 3x + 3x = 6x 4 + 6x = 16 + -3x + 3x Combine like terms: -3x + 3x = 0 4 + 6x = 16 + 0 4 + 6x = 16 Add '-4' to each side of the equation. 4 + -4 + 6x = 16 + -4 Combine like terms: 4 + -4 = 0 0 + 6x = 16 + -4 6x = 16 + -4 Combine like terms: 16 + -4 = 12 6x = 12 Divide each side by '6'. x = 2 Simplifying x = 2
| 4-7x=5x+148 | | (3+6g)12= | | 3x-9=7x-9 | | y=x^2+10x+16 | | 12+12y=10y-12 | | 4x-20+3x+15=100 | | 9-7x=-x-39 | | -5+3x=x-7 | | 9x+16=0 | | 2n(7n+8)=n+8 | | (x+a)(x+b)=(x+c)(x+d) | | 48-4x=5x+16 | | -28-10x=7x+23 | | 2x+10=-12-9x | | 4[3t+8]=3a+12 | | .2x-8=-2-1 | | [3x-7]-5=-3 | | x^4-12x^2-64=0 | | 5x-3=14x+5 | | 1.6q-4.5-4.5q=-3.9q-4.4 | | [5x+9]+6=1 | | 4x-20+3x+13=100 | | 4b-8=10-b | | x^4+8x^2+15=0 | | 4(h+1)=2(5h+6) | | 8x^5-25y^3+80x^4-x^2y^2+20x^3-10xy^3=0 | | 6x+27=13x-57 | | 6x+4x+4+9=7x+3+2x | | 8(x+1)=9+8x | | [a-3]-14=-6 | | 4x+4-1=-9x+7 | | 3ax-2=5bx+7 |